Strategies for palliative care for young patients with advance cancer (年轻晚期癌症患者的临终关怀护理对策) - NI Chunyan (倪春燕); WU Fang (吴芳); ZHOU Qiong (周琼); LI Huifen (李惠芬) (Association of Integrative Nursing, 2022)
This paper analyzed the mental status and health needs of young patients with advance cancer. A brief summary of strategies about psychological support, death education, symptomatic treatment and end-of-life care was provided, in order to provide the quality of palliative care for young patients with advance cancer. (本文分析晚期癌症患者的特殊心理及需求, 通过提供对年轻晚期癌症临终患者及照护者心理支持、死亡教育、对症治疗和生活照护等手段, 提高年轻晚期癌症患者临终阶段的生存质量。)